2015
DOI: 10.3109/02770903.2015.1020389
|View full text |Cite
|
Sign up to set email alerts
|

Age at asthma onset and asthma self-management education among adults in the United States

Abstract: Objective Asthma self-management education improves asthma-related outcomes. We conducted this analysis to evaluate variation in the percentages of adults with active asthma reporting components of asthma self-management education by age at asthma onset. Methods Data from 2011 to 2012 Asthma Call-back Surveys were used to estimate percentages of adults with active asthma reporting six components of asthma self-management education. Components of asthma self-management education include having been taught to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Collider bias 24, 35 might have affected our results regarding relationships between health care access (e.g., cost as a barrier to seeing a doctor for asthma) and asthma-related hospitalizations or ED/UCV, because the selection of individuals with active asthma was partially predicated on potentially overlapping attributes (e.g., talked to a doctor or other health professional about asthma in the past 12 months). 1618 The content of the BRFSS and ACBS questionnaires limited investigation of other potential contributors to asthma morbidity and precluded distinguishing between emergency department and urgent care center visits. Data on IgE sensitization were not collected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collider bias 24, 35 might have affected our results regarding relationships between health care access (e.g., cost as a barrier to seeing a doctor for asthma) and asthma-related hospitalizations or ED/UCV, because the selection of individuals with active asthma was partially predicated on potentially overlapping attributes (e.g., talked to a doctor or other health professional about asthma in the past 12 months). 1618 The content of the BRFSS and ACBS questionnaires limited investigation of other potential contributors to asthma morbidity and precluded distinguishing between emergency department and urgent care center visits. Data on IgE sensitization were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…This study was focused on adults aged ≥65 years with active asthma (Figure 1). As in previous analyses of BRFSS and ACBS data, 1618 respondents were classified as having active asthma if they reported in ACBS that at least one of the following occurred during the past 12 months: talked to a doctor or other health professional about his or her asthma, took asthma medication, or experienced any symptoms of asthma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A self-management is quite critical to achieving optimum asthma treatment goals. The Latest studies have found that training in asthma selfmanagement, which involves a number of varied factors, such as a self-monitoring activity, a regular medical review, and a written action plan, appears to improve health outcomes for patients with asthma (Mirabelli et al, 2015). One of the many effective ways proposed to help improve the outcomes of self-management in patients with asthma is through the use of smartphone applications.…”
Section: Introductionmentioning
confidence: 99%